A case of Stevens-Johnson syndrome due to rifampicin - Badar, Vandana A.; Mishra, Dharmendra; Deshmukh, Swapnil; Chaudhari, Sangita (International Journal of Basic & Clinical Pharmacology, 2017)
A 25 year old female known case of category II pulmonary Tuberculosis was on anti-coch’s treatment in the FDC of rifampicin, isoniazid, pyrazinamide, ethambutol and Streptomycin. Fifteen days after the commencement of Cat II anti TB treatment she developed diffuse erythematous rash on face, trunk and both extremities which turned into blisters. There were ulcers on oral and genital cavity. A diagnosis of Stevens Johnson’s syndrome was made. The patient had a history of cat I pulmonary TB and treated for 8 months and at the end of 8th month she was sputum smear negative. Four months later she had a relapse of sputum smear positive for pulmonary TB. She responded to the stoppage of drugs and oral/inj. Corticosteroids, antihistaminics and antibiotics.